Analisis Penerapan Metode Profile Matching dan Weighted Product Dalam Pemilihan Karyawan Terbaik (Studi Kasus : Mini Market Hidayah) - Ramadhan, Ramadhan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Mini Market Hidayah (MM Hidayah) is a cooperative company engaged in sembako. So far MM Hidayah has evaluated the performance of its employees on things that are growing only, but has never done the best employee selection. Therefore, a computerized system is needed that can provide convenience in determining the best employees. Therefore, a computerized system is needed that can provide convenience in determining the best employees. In this study proposed a computerized system that can help in the selection of the best employees, namely using profile matching methods and weighted product methods. The Profile Matching method is the process of comparing or matching profiles between individual competencies into the ideal variable predictor level competencies that must be met by the subjects studied. While Weighted Product uses multiplication to connect attribute ratings, where the rating of each attribute must be raised first with the weight of the attribute in question, the process is the same as normalization. The Profile Matching method is used for combat values while weigthed product to determine weighting criteria. If the decision-making process is assisted by a computerized decision support system, it is expected that subjectivity in decision making can be reduced and replaced by the implementation of assessment criteria for all employees.